The contribution of testbeds in sustainable innovation : a case study of aquaponics in Sweden - Demmer, Maximilian (SLU/Dept. of Economics, 2022)
Aquaponics has gained increasing popularity as it offers a more sustainable solution to farm fish and leafy greens sustainably and closer to urban centres. While generally seen as a real potential to improve sustainable food production, the commercialisation of aquaponics globally is though still at its beginnings. Aquaponics stands nowadays at a point being currently mostly tested through testbeds, which can be defined as facilities or similar for testing something in development its real-world context. This study assesses the application of a such a testbed facility in the process of creating a sustainable innovative food production system at the start-up Johannas Stadsodlingar AB in the north of Stockholm, Sweden. Through conducting semi-structured interviews and a qualitative content analysis the following four main themes for the application of a testbed in the context aquaponics are found: 1. An insufficient technological readiness level, leading to a need for proof of concept; 2. Learnings and the overcoming of technical challenges a testbed offers; 3. Reducing risk & building up self-confidence in the system; 4. The demonstration purposes and social influence on people a testbed has. In sum, it can be said that testbeds contribute as an efficient tool in the context of sustainable innovation. Testbeds can serve as very important demonstrating and signalling tools to all stakeholders. They make it possible to develop and achieve innovations in a simulated real-world context before scaling them and making them market ready.